2022
DOI: 10.1016/j.ajo.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes in Fellow Eyes Comparing DSAEK and DMEK for Treatment of Fuchs Corneal Dystrophy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(61 reference statements)
0
12
2
Order By: Relevance
“…Our study confirmed that previously reported short-term and mid-term high visual acuity levels were maintained up to 10 years after DMEK. 2,7,9,10 Interestingly, 10-year BCVA values reported for our large DMEK cohort were slightly worse than those for the earlier reported very first 100 DMEK cases that are included in the current cohort (0.08 vs. 0.03 logMAR). 6 This difference could be attributed to the overall worse preoperative BCVA and higher preoperative pachymetry values in our current study, which reflects that the surgical indication had shifted over time from moderate FECD to more advanced FECD and more BK cases (2% BK cases in the first 100 cases 6 to 9% BK cases in the current cohort).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our study confirmed that previously reported short-term and mid-term high visual acuity levels were maintained up to 10 years after DMEK. 2,7,9,10 Interestingly, 10-year BCVA values reported for our large DMEK cohort were slightly worse than those for the earlier reported very first 100 DMEK cases that are included in the current cohort (0.08 vs. 0.03 logMAR). 6 This difference could be attributed to the overall worse preoperative BCVA and higher preoperative pachymetry values in our current study, which reflects that the surgical indication had shifted over time from moderate FECD to more advanced FECD and more BK cases (2% BK cases in the first 100 cases 6 to 9% BK cases in the current cohort).…”
Section: Discussioncontrasting
confidence: 70%
“…D escemet membrane endothelial keratoplasty (DMEK) has proven to be a successful treatment option for corneal endothelial disorders, [1][2][3][4][5][6][7] with Fuchs endothelial corneal dystrophy (FECD) and bullous keratopathy (BK) being the main surgical indications. [8][9][10] Clinical outcomes after DMEK are often reported on a heterogeneous patient pool of different surgical indications; however, some studies have reported an influence of surgical indications on shortterm and mid-term outcomes. 8,10 The different surgical indications could potentially influence the longer-term clinical outcomes and graft survival rates as well.…”
mentioning
confidence: 99%
“…23 Multiple studies have tried to reduce the exposure to colorants. 24 In this study, we compared pairs of corneas aiming to reduce the differences in the results. 25,26 The improved visualization of the glasses-assisted 3D display system enabled a good quality stripping the DMEK tissues while reducing the staining time to 5 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Finally, DSAEK is often the most appropriate surgical choice for complicated eyes, including aphakic eyes, eyes with hyperdeep anterior chambers, eyes that have undergone pars plana vitrectomy, eyes with glaucoma drainage devices, or eyes with large iris defects. 9,11…”
mentioning
confidence: 99%
“…9 For some surgeons, DSAEK is also often the procedure of choice for less compliant patients because of the need for closer postoperative follow-up and the potential for rebubble procedures with the DMEK procedure. 9,11 Finally, DSAEK is often the most appropriate surgical choice for complicated eyes, including aphakic eyes, eyes with hyperdeep anterior chambers, eyes that have undergone pars plana vitrectomy, eyes with glaucoma drainage devices, or eyes with large iris defects. 9,11 DSAEK surgery requires removal of the recipient Descemet membrane and insertion of donor tissue.…”
mentioning
confidence: 99%